Model of Job Satisfaction and Organizational Commitment - Setiawan, Heri; Herawati, Yusleli; Alhadi, Esya; Sayuti, A. Jalaludin; Rini, Rini; Bustan, Jusmawi; Desiana, Lidia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This research focuses on task-oriented leadership styles that have paid very little attention, especially in assessing the impact of task-oriented leadership styles. leadership style on psychological capital, job satisfaction and employee organizational commitment. This research further develops research on the relationship between leadership style, psychological capital, job satisfaction and employee organizational commitment in SMEs in Indonesia, especially in the city of Palembang.The research design is a research plan, namely a detailed explanation of the entire research plan starting from the formulation of the problem, objectives, description of the relationship between variables. The number of samples in this study was 180. It was found that the leadership style variable had an effect on job satisfaction, the psychological capital variable had an effect on satisfaction work, leadership style variables affect organizational commitment, psychological capital variables affect organizational commitment, and job satisfaction variables affect organizational commitment